Pengaruh Pembiasaan Menulis Al-Qur’an Dan Motivasi Belajar Terhadap Pembentukan Karakter Disiplin Siswa Di Madrasah Tsanawiyah Smesta 789 Yayasan Islam Fajar Shodiq Mojokerto - Furoida, Media Asni (Pendidikan Islam Pascasarjana IAIN Jember, 2025)
Technological advancements are increasingly sophisticated, particularly concerning moral and religious aspects. For the majority of Muslims, writing the Quran is something very challenging. Using the follow-the-line method, the habit of Quran writing aims to train individuals to write Quranic verses by following the provided lines. The objectives of this research is To determine whether the habit of Quran writing and learning motivation influence the formation of disciplined character among students at Madrasah Tsanawiyah Smesta 789 Mojokerto. This research adopts a quantitative approach with a survey research design. The results of this research using multiple linear regression show that there is a positive and significant influence between the habit of Quran writing and learningmotivation on the formation of discipline character among students, with an F value of 21.963 > F table 3.12 and significance of 0.000 < 0.05, with an influence of 35.9% according to the Adjusted R-square test result.